Differences in Physician Referral Drive Disparities in Surgical Intervention for Hepatocellular Carcinoma: A Retrospective Cohort Study. Issue 2 (February 2016) - Chidi, Alexis P.; Bryce, Cindy L.; Myaskovsky, Larissa; Fine, Michael J.; Geller, David A.; Landsittel, Douglas P.; Tsung, Allan
Abstract : Objective: To determine whether sociodemographic and geographic factors are associated with referral for surgery and receipt of recommended surgical intervention. Background: Surgical interventions confer survival advantages compared with palliative therapies for hepatocellular carcinoma (HCC), but disparities exist in use of surgical intervention. Few have investigated referral for surgery as a potential barrier to surgical intervention, and little is known about the effects of patient geographic factors, including proximity to surgical centers. Methods: Data were abstracted from the Pennsylvania Cancer Registry for patients with a diagnosis of HCC from 2006 to 2011. Using hospital procedure volume data from the Pennsylvania Health Care Cost Containment Council, we calculated proximity to a surgical center. We used multivariable logistic regression to determine whether geographic, racial, socioeconomic, and clinical factors were associated with referral for surgery and receipt of a recommended surgical intervention. Results: Of 3576 patients with HCC, 41.0% were referred for surgery. Patients who lived closer to a surgical center were less likely to be referred for surgery (adjusted odds ratio = 0.79; 95% confidence interval, 0.68–0.92). Surgical referral was less likely among older, male patients with Medicaid insurance and advanced tumor stage at diagnosis. Of those referred, 1276 (87.0%) underwent surgical intervention. Proximity to a surgical center was not associated with receipt of surgical intervention ( P  = 0.27). Patients with distant tumor stage at diagnosis were less likely to receive recommended surgical intervention (adjusted odds ratio = 0.27; 95% confidence interval, 0.15–0.50). Conclusions: Geographic and sociodemographic disparities in referral for surgery may be major barriers to surgical intervention for patients with HCC.